Increasing access to prevention of mother-to-child transmission of HIV services through the private sector in Uganda. Issue 7 (24th August 2009) - Mbonye, A K; Hansen, K S; Wamono, F; Magnussen, P
Abstract : Objectives: To explore whether private midwives can perform HIV counselling and testing, provide antiretroviral treatment and contraceptives, and how this affects access to services especially among young and HIV-positive women. Methods: A formative study was conducted between January and April 2009 to assess care-seeking practices and perceptions on the prevention of mother-to-child transmission (PMTCT) and family planning services in Wakiso district, central Uganda. A household survey supplemented by 12 focus group discussions and 66 key informant interviews was carried out between January and April 2009. Results: 10 706 women, mean age 25.8 years (14–49 years) were interviewed. The majority of women, 4786 (57%) were in the lowest wealth quintile; 62.0% were not using family planning (p<0.000); 56.2% did not access HIV counselling and testing because they feared knowing their HIV status (p<0.013), while 66.5% feared spouses knowing their HIV status (p<0.013). Access to these services among the young women and those with no education was also poor. Private midwives provide HIV testing to 7.8% of their clients; 5.9% received antiretroviral drugs and 8.6% received contraceptives. Client satisfaction with services at private midwifery practices was high. Private midwives are trusted and many clients confide in them. An intervention through private midwives was perceived to improve access because of short distances and no transport costs. Adolescents prioritised confidentiality, while subsidising costs, community sensitisation and focusing on male spouses were overwhelmingly recommended. Conclusions: Private midwives clinics are potential delivery outlets for PMTCT in Uganda. A well-designed intervention linking them to the public sector and the community could increase access to services.